HUBUNGAN ANTARA MOTIVASI DAN KEBIASAAN BELAJAR TERHADAP PEMAHAMAN KONSEP MATEMATIS MAHASISWA PENDIDIKAN MATEMATIKA - Hidayati Rais; Ferinaldi; Muhammad Ali Basroh (Pendidikan Matematika | STKIP YM Bangko, 2021)
This study aims to determine and describe the significant relationship between motivation and study habits on understanding the mathematical concepts STKIP YPM Bangko mathematics education college students. This type of research is a quantitative approach with a correlational method. The study population was all students in the fifth semester of mathematics education college students STKIP YPM Bangko in the academic year 2020/2021, totaling 16 people. Sampling using saturated sampling technique. The instrument used was a test of understanding mathematical concepts in the algebraic structure course in the form of essays and questionnaires using a Likert scale. The data analysis technique uses the normality test and linearity test, while for the hypothesis test using the Pearson product moment correlation formula, and the multiple correlation formula using the SPSS 20 program. The results of data analysis in the sample class obtained a correlation coefficient of motivation and learning habits variables on understanding mathematical concepts with value sig.F change = 0.122 because the sig.F change value> 0.05 or 0.122> 0.05 means that Ho is accepted and Ha is rejected. This means that there is no significant relationship between motivation and study habits on understanding the mathematical concepts STKIP YPM Bangko mathematics education college students.